TRANSFER OF VEHICLES SI JUKI'S INTELLECTUAL PROPERTY RIGHTSFROM COMICS TO ANIMATION - Kurniawan, Ehwan (UI Scholars Hub, 2020)
Transfer of vehicles is removal and alteration. In a broader meaning, this term can even include the conversion of various types of science into works of art. Intellectual Property Rights are rights granted to the creators of Intellectual Property and include trademarks, copyrights, patents, industrial rights, and in some jurisdictional trade secrets. Art works including music and literature, as well as inventions, words, expressions, symbols, and designs can all be protected as intellectual property. Comics (noun) plural form, used with a single verb. Pictures and other symbols that are overlap (close together, next to each other) in sequentially thing, to provide information and/or achieve aesthetic responses from readers. Animation is a two-dimensional image or three-dimensional model that seems to move, because of the brain's ability to always save/remember images that were seen before. To enjoy the animation how to move a collection of images that are displayed sequentially with a certain speed that creates the impression of moving from the image